Design and implementation of low cost thrust benchmarking system (TBS) in application for small scale electric UAV propeller characterization. (November 2018) - Virginio, R; Fuad, F A; Jihadil, M; Ramadhani, M J; Rafie, M; Stevenson, R; Adiprawita, W
Abstract: Thrust Benchmarking System (TBS), a low cost and easy to manufacture instrument for electric UAV propulsion system performance measurement is being proposed. With one of its uses for determining the static thrust of a propeller based on simple empirical characterization modeling. In this paper, characteristic modeling is performed on 3 APC-Electric propellers with different pitch and diameter dimensions. As a result, there are 2 constants K1 and K2 which can express similar propeller characteristics with different dimensions. It costs IDR 1.6 million and took two-and-a-half months of manufacture and assembly process.